2016
DOI: 10.1002/dvdy.24468
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and pathological roles of fibroblast growth factors in pulmonary diseases

Abstract: Fibroblast growth factors (FGFs) constitute a large family of polypeptides that are involved in many biological processes, ranging from prenatal cell-fate specification and organogenesis to hormonal and metabolic regulation in postnatal life. During embryonic development, these growth factors are important mediators of the crosstalk among ectoderm-, mesoderm-, and endoderm-derived cells, and they instruct the spatial and temporal growth of organs and tissues such as the brain, bone, lung, gut, and others. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 110 publications
(105 reference statements)
2
21
0
Order By: Relevance
“…This is best exemplified in the skin where anatomically different, dermal, and non‐dermal fibroblasts show divergent gene expression patterns that can be attributed to distinct developmental origins such as from somites, neural crest, and dermatomyotome 23 . Similarly, in the lung lineage tracing experiments revealed multiple fibroblast progenitors: Fgf10 lineage mesenchymal cells, 24 Plin2 ‐traced lipofibroblasts, 25 or Tbx4 lineage cells were sources of αSMA‐expressing myofibroblasts and other mesenchymal cell subsets 26 . Data presented by these studies further consolidate the view that subpopulations of fibroblasts vary between and within anatomical locations in gene expression and cell surface markers.…”
Section: Influence Of Developmental and Anatomical Origin On Fibroblast Diversitymentioning
confidence: 99%
“…This is best exemplified in the skin where anatomically different, dermal, and non‐dermal fibroblasts show divergent gene expression patterns that can be attributed to distinct developmental origins such as from somites, neural crest, and dermatomyotome 23 . Similarly, in the lung lineage tracing experiments revealed multiple fibroblast progenitors: Fgf10 lineage mesenchymal cells, 24 Plin2 ‐traced lipofibroblasts, 25 or Tbx4 lineage cells were sources of αSMA‐expressing myofibroblasts and other mesenchymal cell subsets 26 . Data presented by these studies further consolidate the view that subpopulations of fibroblasts vary between and within anatomical locations in gene expression and cell surface markers.…”
Section: Influence Of Developmental and Anatomical Origin On Fibroblast Diversitymentioning
confidence: 99%
“…Further work demonstrated that TAS-115 also inhibits signaling through colony-stimulating factor receptor on macrophages (M-CSFR, or c-FMS) as well as PDGF receptor α (PDGFRα) (9, 10). Unlike nintedanib, TAS-115 appears to spare FGF receptors (FGFRs), which may be beneficial as some FGFs are antifibrotic (11). Given that PDGFs play a key role in promoting fibrosis (12) and that macrophages may also contribute to the disease via elaboration of the profibrotic chemokine CCL-2 (13), the authors elected to focus on PDGFRs and c-FMS in this study.…”
mentioning
confidence: 99%
“…During the lung development process, FGF2 expression pattern is dynamic in different pulmonary cell types, indicating its differential role during the lung development stages. In mouse embryogenesis, mesoderm-derived Fgf1 and Fgf2 are involved in commiting the lung fate at the ventral foregut endoderm on embryonic day 8 (E8) (El Agha et al, 2017).…”
Section: Implications Of Fgf2 In Airway Diseasesmentioning
confidence: 99%